Critical Fantasy Studies: neoliberalism, education and identification - an interview with Jason Glynos - Glynos, Jason; Oliveira, Gustavo Gilson Sousa de; Burity, Joanildo (Série-Estudos, 2019)
Interview with Professor Jason Glynos, co-director of the Center for Ideology and Discourse Analysis (CIDA) at the University of Essex, UK, conducted by professors Joanildo Burity (FUNDAJ) and Gustavo Gilson Oliveira (UFPE). The interview explores the contours, the conceptual framework and the analytic strategies being developed in relation to the so-called Critical Fantasy Studies’ field, associated with his recent work. It seeks to investigate, above all, how these concepts and strategies have contributed and may further contribute to broadening our understanding and deepening our analysis of the spread of neoliberal logics and the emergence of “new” conservative logics in the contemporary social and political scene, particularly in the field of education.